2012
DOI: 10.1158/0008-5472.can-12-0475-t
|View full text |Cite
|
Sign up to set email alerts
|

TMEM16A Induces MAPK and Contributes Directly to Tumorigenesis and Cancer Progression

Abstract: Frequent gene amplification of the receptor-activated calcium-dependent chloride channel TMEM16A (TAOS2 or ANO1) has been reported in several malignancies. However, its involvement in human tumorigenesis has not been previously studied. Here, we show a functional role for TMEM16A in tumor growth. We found TMEM16A overexpression in 80% of head and neck squamous cell carcinoma (SCCHN), which correlated with decreased overall survival in patients with SCCHN. TMEM16A overexpression significantly promoted anchorage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
371
4
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 259 publications
(397 citation statements)
references
References 49 publications
15
371
4
7
Order By: Relevance
“…The complex structure of this amplicon has mostly been studied in breast cancer, where multiple genes have been suggested as driver genes [21,22]. These findings implied a link between Ano1 expression, cell-cycle regulation and proliferation, which has recently been demonstrated in HNSCC and other cancer cells [11,16,[23][24][25]. Surprisingly, downregulation of Ano1 contributes to cerebrovascular remodelling by promoting basilar smooth muscle cell proliferation, which is through inhibition of expression of cyclin D1 and cyclin E [26].…”
Section: Ano1 Is Located On the 11q13 Ampliconmentioning
confidence: 97%
See 1 more Smart Citation
“…The complex structure of this amplicon has mostly been studied in breast cancer, where multiple genes have been suggested as driver genes [21,22]. These findings implied a link between Ano1 expression, cell-cycle regulation and proliferation, which has recently been demonstrated in HNSCC and other cancer cells [11,16,[23][24][25]. Surprisingly, downregulation of Ano1 contributes to cerebrovascular remodelling by promoting basilar smooth muscle cell proliferation, which is through inhibition of expression of cyclin D1 and cyclin E [26].…”
Section: Ano1 Is Located On the 11q13 Ampliconmentioning
confidence: 97%
“…HDAC inhibitors promote expression of p21 in breast cancer cells, which inhibits the action of cyclin D1. HDAC inhibitors may therefore also be useful for the treatment of those HNSCC that show overexpression of Ano1 and concomitant activation of cyclin D1 [23]. In fact, HDAC inhibitors have already entered preclinical evaluation [42,43].…”
Section: Regulation Of Expression Of Ano1 By Histone Deacetylase and mentioning
confidence: 99%
“…A pro-proliferative role of ANO1 is found in most cancer cells investigated 118,[141][142][143][144][145][146] and Stanich and coworkers demonstrated that ANO1 regulates cell proliferation at the G1/S transition in the cell cycle. 147 Other studies, however, show that cell proliferation in certain cell types is unaffected by ANO1, e.g.…”
Section: Proliferationmentioning
confidence: 99%
“…120 ANO1 knockdown resulted in a decreased migratory rate. Although many studies have shown the importance of ANO1 in migration 137,139,141,145,146,156 there are also studies demonstrating that ANO1 might act indirectly. Thus, Ubby et al overexpressed ANO1 in HEK293 cells and measured large ANO1-like currents, but no effect on migration was observed.…”
Section: Migration and Metastasismentioning
confidence: 99%
“…The identification of activators and inhibitors in low molecular weight compound screens suggests that chemical modification of ANO1 function is feasible, making it a promising therapeutic target (24)(25)(26). Recently, ANO1 has been found to contribute to HNSCC tumorigenesis and invasion (27)(28)(29). In contrast, the effects of ANO1 in breast cancer, its functional activity in tumorigenesis, and whether it is required for tumor maintenance have remained elusive.…”
mentioning
confidence: 99%